Comparison of Intra-Annual Xylem and Phloem Formation of Picea crassifolia Stands at Two Latitudes in Northwest China - Biyun Yu (MDPI AG, 2021)
Understanding the changes in xylem and phloem formation of trees and their relationship along latitudes are important for evaluating and predicting how fragile forests may respond to climate change; however, corresponding studies are still relatively scarce. This study investigated the intra-annual dynamics of xylem and phloem formation of Picea crassifolia and their relationship at two latitudes of arid and semi-arid forests in China. The results showed that both xylem and phloem formation varied at different latitudes. Xylem formation at the low-latitude site (Luoshan) started two weeks earlier than that at the high-latitude site (Helanshan) but ended one week later, resulting in an extended growing season at the low-latitude site. Phloem formation preceded cambium activity and xylogenesis at both sites by 24.6 days in Luoshan, which had warmer conditions, and by 17.3 days in Helanshan. In Luoshan, compared to Helanshan, there occurred significantly more enlarging and wall thickening cells, during (relatively wet) June–August, but significantly fewer enlarging and wall thickening cells as well as total xylem cells, during (relatively dry) April–May. Sample trees produced significantly fewer early phloem cells during the early growing season (April–May) in Luoshan, but generated significantly more late phloem cells during the late growing season in Helanshan. Additionally, different trade-offs between xylem and phloem formation were observed at different sites. The longer duration of early phloem formation might have shortened the duration of xylem lignification in Helanshan; in Luoshan, the date that late phloem reached its maximum growth rate was significantly positively correlated with the date when xylem lignification ended. The results revealed the plasticity of xylem and phloem formation under changing environmental conditions and a complex and site-specific relationship between xylem and phloem formation. These findings could help us better understand and predict the future growth of arid and semi-arid forests in China in response to climate change.